(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
The temporary proximal loop or end ileostomy is considered suitable to protect a distal anastomosis following surgery for gangrene or perforation of terminal ileum with faecal peritonitis and colorectal surgery. This technique is, however, associated with failure, complications and even mortality. The aim of this study was to quantify retrospectively the morbidity associated with an ileostomy and its subsequent closure. Fifty patients with a temporary ileostomy, created between July 2007 and December 2009 were retrospectively analyzed from a review of patient records. All operations of ileostomy closure were done after a median period of 106 days (interquartile range: 69174 days). Stoma related morbidity occurred in 26(52%) patients. After ileostomy closure, 21 major complications were seen in 10(20%) patients and 28 minor complications occurred in 17(34%) patients. Sixteen (32%) patients had neither stoma-related morbidity or peri- or postoperative complications after stoma closure. Protective proximal ileostomy was found to be associated with a high morbidity. This raises the question of the mode of identifying the specific patients with an ileal perforation/gangrene or low anastomosis who should be provided an ileostomy for protection, set against the potential complications of the formation and closure of the ileostomy. DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11325 J Bangladesh Coll Phys Surg 2011; 29: 196-200